Magneto-Radiative Interactions on Boundary Layer Development: Heat Transfer and Skin Friction Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study presents a comprehensive numerical investigation into the boundary layer behavior of an electrically conducting fluid influenced by simultaneous magnetic and radiative effects over an exponentially stretching surface. The analysis focuses on the impacts of magnetic field intensity, thermal radiation, and Prandtl number on the velocity, temperature distribution, skin friction coefficient, and heat transfer rate. A system of coupled nonlinear differential equations governing the momentum and energy transport is formulated and solved using MATLAB’s bvp4c solver. Results reveal that increasing magnetic field strength significantly reduces fluid velocity due to the Lorentz force, while enhancing the temperature profile through magnetic damping. Similarly, stronger thermal radiation increases fluid temperature and thickens the thermal boundary layer, though it reduces the Nusselt number by diminishing surface temperature gradients. In contrast, higher Prandtl numbers lead to lower temperatures and enhanced heat transfer without substantially affecting skin friction. These findings highlight the critical interplay of magnetic and radiative phenomena in modifying boundary layer characteristics, offering practical insights for the design and optimization of advanced thermal systems in materials processing, energy harvesting, and magnetic insulation technologies.